Total vertebrectomy through posterior approach for thoracic tumors - Jefferson Soares Leal; Rogério Lúcio Chaves de Resende; Daniel Ferreira Ghedini; Leandro Vinícius Vital; Haroldo Oliveira de Freitas Júnior; Luiz Eduardo Moreira Teixeira (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Objective: To demonstrate the benefits and complications of the single posterior approach through bilateral costotransversectomy in the treatment of neoplastic disease of the thoracic spine. Methods: Twelve consecutive patients with thoracic spine tumors, who underwent single posterior approach with bilateral costotransversectomies were reviewed. Through posterior extrapleural access, total vertebrectomy and reconstruction were performed. In reconstruction, a cage was used anteriorly, and a pedicular screw fixation was used posteriorly. The minimum follow-up was sixteen months. The parameters analyzed were pain, neurological and functional capacity, survival time, fixation stability, and complications.  Results: All patients had improvement in their pain or in their functional capability. Among those with a preoperative neurological deficit, 71.4% showed improvement of at least one degree at postoperative evaluation. There was no functional or neurological decline in any patient. The observed complications were: one adult respiratory stress syndrome, one excessive bleeding, one pneumothorax, one infection and one local recurrence. All but one of these complications was reversed with appropriate treatment.  Conclusion: The posterolateral approach through costotransversectomy was safe and secure method for the resection and reconstruction of thoracic vertebrae affected by neoplastic disease.